Overcoming Health Risk of Down Syndrome Child with Obesity: Systematic Review - Prita Dhyani Swamilaksita (Journal of ICSAR, 2022)
Down syndrome (DS) is a condition that occurs due to an abnormal number of chromosomes which is characterized by the presence of an additional chromosome. A child diagnosed with DS has three distinctive characters, namely having a low Intelligence Quotient (IQ), physical and mental limitations and having a weak immune system. Overweight and obesity are nutritional problems that often occur in people with DS, so it is necessary to study how the health risks that can be experienced by DS sufferers with obesity and how to overcome or minimize these risks. This Systematic Review study was conducted using the PubMed/Medline, Science Direct, and Google Scholar search databases. The search was limited to articles in peer-reviewed journals and literature reviews, which were written in English and Indonesian between 2012 and 2022. The study results showed that more than 40 percent of obesity occurred in children with DS. Obesity in people with DS can increase the risk of other health problems such as Obstructive Sleep Apnea (OSA) in adults with DS. In addition, dyslipidemia, hyperinsulinemia, NAFLD, Alzheimer's and tumors, and coronary heart disease are frequently reported in obese DS. Therefore, it is necessary to prevent nutritional problems by parents which includes parenting, feeding practices, and eating patterns. In addition, physical activity is needed for children with DS, especially for those who suffer from obesity. Fulfillment of nutrition and a healthy lifestyle throughout pregnancy is also needed to ensure the health of the child born and reduce the risk of having a baby with DS.